Pengaruh Perceive Organizational Support dan Core Self Evaluation terhadap Job Per-formance Melalui Job Engagement dan Organizational Citizenship Behavior (Studi pa-da: Karyawan Tetap PT. Anomali Coffee Indonesia) - Priska C. Hatta; Paulina Paulina (STIE Indonesia Banking School, 2019)
Indonesia as the largest coffee producer in the world, but Indonesia citizens prefer to consume coffee from other countries rather than Indonesia coffee. The purpose of this study is to know the influence of per-ceived organizational support and core self-evaluation on job performance through job engagement and organizational citizenship behaviour. This research is categorized as survey research with descriptive analysis method by taking a sample and using a questionnaire as the main data. The sample has been col-lect 142 employees from 250 employees of PT. Anomali Coffee Indonesia. The respondents are chosen by using non-probability sampling and convenience sampling techniques. The results of the analysis using Structural Equation Modeling (SEM) and its result would be summarized as below: 1). Perceive Organiza-tional has positive and significant Job Engagement 2). Core Self Evaluation has positive and significant to Job Engagement 3). Job Engagement has positive and significant to Organizational Citizenship Behavior 4). Organizational Citizenship Behavior has positive and significant to Job Performance.